Society in the Digital Age: Creating a Positive Impact Through Sustainable Digital Marketing Practices - Kariyamin; Rahmat Ardila Dwi Yulianto; Muhammad Kunta Biddinika; Anthon Yudhana (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
In the ever-evolving digital era, digital marketing practices have become an important component for businesses and organizations in various sectors. However, it is important for us to consider the impact generated by these digital marketing practices. It is important for us to ensure that these practices are not only effective in achieving marketing goals, but also sustainable and have a positive impact.The purpose of this digital marketing training is to provide students with more in-depth knowledge that digital has a positive and sustainable impact. The implementation of the training activities was carried out at SMK Miftahul Huda Sambungmacan Sragen on Friday, June 9 2023. The method of implementation was the lecture and discussion method. The results of this activity based on the results of the questionnaire are the increased understanding of students at SMK Miftahul Huda Kontakmacan Sragen regarding digital marketing. The implementation of this activity went well where the training participants actively participated in the activity from start to finish and were able to do the exercises properly and on time, which meant that participants could understand the material presented well.